Adverse Reactions due to the Usage Ofadverse Effects due to the Usage of T biomodulina and corticotropin in Patients Suffering from Multiple Sclerosis - Rosa F. Lara Rodríguez; Roman Rodríguez; Alicia Vargas Batista; Miriam Bolet Arostavista; Rebeca A. Fernández Carriera; Idalmis Suárez Luis; Alina González-Quevedo Monteagudo; Lorenzo Gómez Morales (Medisur)
Background: T biomodulina is a thymic natural product with anti-inflammatory and immunomodulator action. Corticotropin is a steroid which is also used in the treatment of multiple sclerosis. Objetives: To compare the adverse effects of the biomodulina and corticotroprin in the treatment of multiple sclerosis. Methods: Phase II clinical trial, open, randomized and controlled on 17 patients suffering from multiple sclerosis to whom the following treatment was applied: group one, 100mg IV biomodulina during 10 days, 20 mg the following 20 days; group two: 1 mg of corticotroprin during 10 days followed by 0,5 mg the very next 20 days. The adverse events were evaluated from the 10th day up to the 30th day classifying its intensity as absent, mild, moderate, severe, very severe. The duration and the type of event were also classified. Results: Safeness on 8 patients treated with biomodulina and 7 patients treated with cortcotropin were assessed. 40 adverse events took place: 24 patients in whose corticotropin was used, 16 in the treatment with biomodulina (80 and 53, 3% respectively), while the moderate adverse reactions in the usage of corticotropin were more frequent. The shorter period of time of the events was produced by biomodulina. Conclusions: The usage of biomodulina was safer in the treatment of multiple sclerosis because the adverse events as well as the period of time were less intense.